1999
DOI: 10.1002/(sici)1097-4644(19990401)73:1<114::aid-jcb13>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Transient upregulation of CBFA1 in response to bone morphogenetic protein-2 and transforming growth factor ?1 in C2C12 myogenic cells coincides with suppression of the myogenic phenotype but is not sufficient for osteoblast differentiation

Abstract: The bone morphogenetic protein (BMP)-2 is a potent osteoinductive signal, inducing bone formation in vivo and osteoblast differentiation from non-osseous cells in vitro. The runt domain-related protein Cbfa1/PEBP2alphaA/AML-3 is a critical component of bone formation in vivo and transcriptional regulator of osteoblast differentiation. To investigate the relationship between the extracellular BMP-2 signal, Cbfa1, and osteogenesis, we examined expression of Cbfa1 and osteoblastic genes during the BMP-2 induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
104
2
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 239 publications
(122 citation statements)
references
References 58 publications
13
104
2
3
Order By: Relevance
“…Several of these genes function in osteoblasts: the transcription factor, Osf2 (cluster 1,2) (9) and the osteoblast matrix proteins, osteomodulin/osteoadherin (Omd; cluster 1,1) (34) and osteoglycin (Ogn; cluster 1,3) (32). Osf2 (Cbfa1) mRNA expression is increased by BMP treatment of C2C12 cells, which causes a transformation from myogenic to osteoblast differentiation (23). The induction of Osf2 transcripts in differentiating C2C12 myoblasts that was observed in our study has not been observed by others.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these genes function in osteoblasts: the transcription factor, Osf2 (cluster 1,2) (9) and the osteoblast matrix proteins, osteomodulin/osteoadherin (Omd; cluster 1,1) (34) and osteoglycin (Ogn; cluster 1,3) (32). Osf2 (Cbfa1) mRNA expression is increased by BMP treatment of C2C12 cells, which causes a transformation from myogenic to osteoblast differentiation (23). The induction of Osf2 transcripts in differentiating C2C12 myoblasts that was observed in our study has not been observed by others.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Cbfa1 is necessary but not sufficient for osteogenic differentiation (32). For example, both BMP-2 and TGF-␤ can induce expression of Cbfa1 and homeodomain proteins in the nonosseous myogenic cell line C2C12 (6,32), but only BMP-2 can support a change to the osteogenic phenotype with concomitant expression of OC and other osteoblast markers (27). Thus Cbfa1 may be inducing or interacting with an unknown factor in response to BMP-2 that functions as a transcriptional activator, either directly as a DNA binding protein or indirectly as a Cbfa partner protein.…”
Section: Discussionmentioning
confidence: 99%
“…1. The upper strands (200 ng) of the oligonucleotides were labeled with 32 P for 1 h at 37°C in a 50-l volume using T4 Polynucleotide Kinase (New England BioLabs, Beverly, Mass.) as indicated by the manufacturer.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the presence of BMP2, proliferating mesenchymal multipotent C2C12 cells can differentiate to the osteoblast lineage, as reflected by expression of early and late bone-related markers (44,48,49). In contrast, when pre-confluent C2C12 cells are grown in the presence of low serum media (e.g.…”
Section: Expression and Repression Of The Runx2/p57 Gene In Mesenchymmentioning
confidence: 99%